Disaster preparedness kits ready or not? Household resilience to flash flooding in Uttarakhand - Praveen Maghelal; Sudha Arlikatti (Heliyon)
The State of Uttarakhand, located in the Himalayan region of North India, suffered one of the worst flash floods on June 16, 2013 where 5700 were presumed dead or missing. Since then, the region has suffered two other major flooding events in 2021 and 2023. Although numerous national government agencies recommend keeping disaster preparedness kits ready, the saliency and effectiveness of a household disaster preparedness kit in helping survivors, has not been empirically tested in the region. Responses to “items they took with them when they evacuated for the flash flood” from 316 households were analysed. Majority were not prepared for evacuation with essentials like food, water, hygiene kits and items for children and the aged, and totally dependent on first responder agencies to come to their rescue. Our findings help to underscore the need to: 1) Ensure disaster kits are recommended by every Panchayat for local at-risk communities and handed to visitors/tourists at points of entry. 2) Revive the National School Safety Programme (NSSP) to help school children create disaster preparedness kits. 3) Conduct additional empirical research in various disaster contexts around the country to demonstrate the benefits for immediate survival and increasing household resilience.